Petroselinum sativum (perejil) antioxidant and hepatoprotective effects in rats with paracetamolinduced hepatic intoxication - Troncoso, Luzmila (2007)
Objective: To determine the antioxidant and hepatoprotective effect of parsley (Petroselinum sativum) in rats with paracetamol-induced hepatic intoxication. Setting: Leonidas Delgado Butron - Emilio Guija Poma Clinical and Nutritional Biochemistry Laboratory, Biochemistry and Nutrition Research Center, Universidad Nacional Mayor de San Marcos, Lima, Peru. Design: Analytical, transverse, prospective and quasi-experimental study; only ‘post’ with quasi-control group design. Biologic materials: Adult male Holtzman albino rats. Methods: We utilized forty 2 months-old adult rats weighing 280 to 320 g distributed at random in four groups 10 animals each. All groups received the same ad libitum diet and water along with respective treatments administered orally daily during 5 days: paracetamol was administered 200 mg/kg pc) to induce hepatic intoxication and concurrently a pharmacologic (hepatoprotective drug (HPD): Purinor®) or natural (parsley) hepatoprotector; another group was treated with paracetamol only and there was a control group. The animals were sacrificed at the end of the experimental period. We determined in serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma glutamyl transferase (GGT), sulphidril group, total proteins and serum albumin; and in liver postmitochondrial fraction cytosolic homogenates we determined superoxide dismutase, catalase, glucose-6-phosphate deydrogenase, sulphidril group, thiobarbituric acid reactive species (TBARS) or free radicals and proteins. Besides, histology study of the liver was done to identify both signs of necrosis and postnecrotic regeneration. Main outcome measures: Parsley’s antioxidant and hepatoprotective effects. Results: Parsley showed a better hepatoprotective effect than HPD against paracetamol’s nocive effect, as evaluated by AST, ALT and GGT serum levels. Determination of glucose-6-phosphate dehydrogenase (p<0,05, p=0,01, Kruskal-Wallis test) and TBARS (p<0,001, p=0,000; Kruskal-Wallis test) in liver cytosolic showed the existence of statistically significant difference among all groups. On histology we observed signs of severe necrosis after administration of paracetamol alone and in the group with additional HPD, with no further changes in the group treated additionally with parsley. Conclusions: Parsley exerts a greater antioxidant and hepatoprotective effect than HPD.